Development of compressive strength of slag based cement mortars exposed to an aggressive sulphate environment - Estokova, Adriana; Smolakova, Michaela; Luptakova, Alena (International Conference “Environmental Engineering”, 2017)
Sulfuric acid corrosion can cause severe damage to concrete and cement composites. There are a variety of approaches to enhancing the sustainability of concrete and mortar one of which is to enhance the durability of concrete using different cement replacement. Granulated blast furnace slag is used in mortar and concrete, as a partial replacement of Portland cement, and this use has resulted in significant savings in the cost of production of concrete. Moreover the use of conventional concrete is notoriously subject to durability and corrosion issues. Laboratory experiments were conducted to investigate the compressive strength of cement mortars samples with cement partially replaced by blast furnace slag. The samples with different share of slag (65, 75, 85 and 95 wt.%) were exposed to a bacterial sulphate environment for 90 days. A decrease in compressive strengths of reference samples by 8% as well as an increase in compressive strengths of all slag-based sampless up to 95 % have been observed. Surface structure and chemical com positions of cement mortars´ leachates confirmed a deterioration process under the microbial exposure of Acidithioba cillus thiooxidans.